Electrorefraction beyond the excitonic resonance in GaAs/AlGaAs multiple quantum well structure in the Franz-Keldysh geometry - Wichtowski, Marek (Photonics Letters of Poland, 2020)
The Kramers-Kronig relations were used to estimate electrorefractivity near the edge of the exciton absorption peak of GaAs/AlGaAs photorefractive quantum well (PMQW) structure working in the Franz-Keldysh geometry. It was shown that for both TE and TM polarizations the change of the refractive index under an applied electric field is at least an order of magnitude greater than in bulk semi-insulating GaAs due to the classical Franz-Keldysh effect. Full Text: PDF References D.D. Nolte, M. R. Melloch in: Photorefractive effects and Materials, ed. by D. D. Nolte (Kluwer, Dordrecht 1995). CrossRef T. E.Van Eck, L. M. Walpita, W.S.C. Chang, H. H. Wieder, "Franz–Keldysh electrorefraction and electroabsorption in bulk InP and GaAs", Appl. Phys. Lett. 48, 451 (1986). CrossRef P.K. Basu, Theory of Optical Processes in Semiconductors, (Oxford University Press, 2003) ch. 7. CrossRef A Partovi. E.M. Garmire, "Band‐edge photorefractivity in semiconductors: Theory and experiment", J. Appl. Phys. 69, 6885 (1991). CrossRef J. S. Weiner, D. A. B. Miller, D. S. Chemla, et. al. "Strong polarization‐sensitive electroabsorption in GaAs/AlGaAs quantum well waveguides", Appl. Phys. Lett. 47, 1148 (1985). CrossRef D. S. Chemla, D. A. B. Miller, "Room-temperature excitonic nonlinear-optical effects in semiconductor quantum-well structures", JOSA A, 2 1155, (1985). CrossRef S.L. Chuang, Physics of Photonic Devices (2-nd ed. New Jersey, Wiley & Sons 2009), ch. 14. DirectLink E. Miśkiewicz, A. Ziółkowski, M. Wichtowski, E. Weinert - Rączka, "Thermally induced changes of the electro-optical properties of semi-insulating GaAs/AlGaAs multiple quantum well structures", Opt. Mat. 89, 231 (2019). CrossRef E.Weinert-Rączka, R.Iwanow, "Asymetric directional coupler controlled by photorefractive grating", Acta Phys. Pol. A 95, 813 (1999). CrossRef